Cell types and synapses expressing the snare complex regulating proteins complexin 1 and complexin 2 in mammalian retina - Lux, Uwe; Ehrenberg, Johanna; Joachimsthaler, Anneka; Atorf, Jenny; Pircher, Bianca; Reim, Kerstin; Kremers, Jan; Gießl, Andreas; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2021)
Complexins (Cplxs) 1 to 4 are components of the presynaptic compartment of chemical synapses where they regulate important steps in synaptic vesicle exocytosis. In the retina, all four Cplxs are present, and while we know a lot about Cplxs 3 and 4, little is known about Cplxs 1 and 2. Here, we performed in situ hybridization experiments and bioinformatics and exploited Cplx 1 and Cplx 2 single-knockout mice combined with immunocytochemistry and light microscopy to characterize in detail the cell type and synapse-specific distribution of Cplx 1 and Cplx 2. We found that Cplx 2 and not Cplx 1 is the main isoform expressed in normal and displaced amacrine cells and ganglion cells in mouse retinae and that amacrine cells seem to operate with a single Cplx isoform at their conventional chemical synapses. Surprising was the finding that retinal function, determined with electroretinographic recordings, was altered in Cplx 1 but not Cplx 2 single-knockout mice. In summary, the results provide an important basis for future studies on the function of Cplxs 1 and 2 in the processing of visual signals in the mammalian retina.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Amacrine cells; Complexin 1; Complexin 2; Conventional chemical synapses; Ganglion cells; Horizontal cells; Retina